Improving low-performing schools through external assistance: Lessons from Chicago and California. - Kara S. Finnigan; Catherine Bitter; Jennifer O'Day (Arizona State University, 2009)
This article describes the design and implementation of external support to low-performing schools using data from Chicago and California. Using the literature on external support, instructional capacity, and policy strength, the study gathered data from interviews, observations, document review, and surveys. The findings suggest that the model of assistance employed in both Chicago and California was inadequate to the task. While the policies examined demonstrate recognition that low-performing schools need additional capacity if they are to substantially improve student outcomes, external support providers used limited and haphazard approaches, and as a result, the support component had little influence on teaching and learning. In addition, because the external supports relied on a market-like support structure with few other mechanisms to ensure quality, and because there was limited quantity (intensity) of support, the benefit that external assistance might otherwise have provided was limited. This was particularly problematic for the lowest capacity schools, many of which experienced limited change despite increased educator effort and involvement of external providers. In essence, external assistance through these school accountability policies did little to improve educator and organizational performance.